Lifting the corporate veil: an examination of the corporate doctrine / Mohd Ghazali M. Taib - M. Taib, Mohd Ghazali (Faculty of Law, 1986)
The company once formed in accordance with the provision of the Act acquires a corporate personality. This is provided in section 14, 15 and 16 of the Malaysian companies Act 1965. In fact in all these section the Act expressly provides for the incorporation of an association of two or more person. History has shown that, since it was formulated "in the case of Soloman v Solomon 1 the concept of separate corporate personality has been affirmed by almost everyone. In that case, Solomon had for many years carried on business as a boot manufacturer. His business was solvent when it was converted into a company, i.e. a company limited by shares was formed, the subscribers to the memorandum of which were Solomon and his wife, daughter and four sons (for one share each), and the business was sold to the company at a price of £39,000,. The term of sale were approved by all the shareholders. £9,000 was paid in cash. 20,000 fully paid shares of £1 each were allotted to Solomon so that his wife and children held one share each and he held 20,001 shares. Solomon left the rest of the price on loan to the company and for this sum of £10,000 he was given debentures 6 secured by a charge of --the company's assets. It seems that the director were Solomon and his sons and that Solomon was appointed managing director. The company ran into difficulties and the company wound up. After satisfying the debentures there was not enough to pay the ordinary creditors.